Long-term symptom improvement and patient satisfaction following catheter ablation of supraventricular tachycardia: insights from the German ablation registry - Brachmann, Johannes; Thomas, Dierk (European heart journal, 2017)
Aims. To analyse outcomes of supraventricular tachycardia (SVT) ablations performed within a prospective German Ablation Quality Registry. Methos and results.